(3GdEYdGe HCYdGe HjJ GGddg GdMQGes - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s ((3eMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeSLO GdMQGe CefkG heKGHI ddfGS hCeQ HJWgjQ GdcYHI GdHjJ GdMQGe ddWGFajf hGdYGcajf hCRGd YfgG GdNha s
(3BNQgG (B:s
(3hbO QCjJ Cf CLYd NJGe gPG GdcJGH eSckG hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejcs
(3ef JhGQjN ecI GdecQeI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs